A systematic literature review of computer ethics issues - Tan, Ming Ming; A. Jabar, Marzanah; Sidi, Fatimah; Koh, Tieng Wei (Asian Research Publication Network, 2015)
Given the importance and concern of computer ethics, four issues have been identified in the field of computer and Information Technology (IT). This study was carried out to review the work done on computer ethics issues for the years 2010 to 2014. This paper identifies the methods used, topics addressed, and the main findings published of the research about ethical issues in computer usage. Systematic literature review (SLR) has been conducted according to the standard guidelines, and a study protocol was applied to answer three research questions: 1) What are the ethical issues in computer ethics that have been discussed in previous research?, 2) What are the most recent topics among computer ethics issues?, and 3) To what extent does investigation among IT students, Non-IT students and IT professionals display different perceptions of IT issues? Based on the evidence extracted from 40 studies, it has been clearly stated that software piracy in Privacy, Accuracy, Property and Accessibility (PAPA) and general issues are the topics most frequently discussed. It shows the gaps in the current literature pertaining to computer ethical issues and in particular, the issue of software piracy.